Factores familiares que influyen en la conducta infractora de los adolescentes pertenecientes al programa justicia juvenil restaurativa del ministerio publico distrito fiscal la libertad, año 2014 - Cusquisiban Sánchez, Alicia Soledad (2015)
This research seeks to understand how family factors influence on adolescent delinquent behavior, the purpose of the study was to implement surveys in order to understand and identify the vision that adolescents before the problem found. This work is part of research the FAMILY FACTORS AFFECTING DELINQUENT BEHAVIOR BELONGING TO ADOLESCENT RESTORATIVE JUVENILE JUSTICE MINISTRY PROGRAM DISTRICT PUBLIC FINANCIAL FREEDOM, YEAR 2014. This research was conducted at the Youth Restorative Justice Program; the sample which intervened was 36 adolescents. The techniques used were: The record of interview, questionnaire and observation log teens program. Therefore aims to determine which family factors that have influenced the offending behavior of adolescents belonging to Juvenile Restorative Justice program are. In this paper the problem actually the first point where the relevance of this research justified by the importance of studies to help understand the negative influence of family factors in adolescent delinquent behavior is dealt is exposed; is also included the theoretical framework used to lay the conceptual basis of this study. Followed the methodology which manifests how the study was conducted, methodology, tools used, statistical design, the overall objective and specific objectives of the research are presented. The results obtained are presented and discussion from the information collected during the development of the research. This point is developed in three chapters: Chapter I, detail the characteristics that adolescents have, such as sex, age and place of origin.